Developing a Bilingual Website Integrated with Social Media for Irgift - Tsabita El Rizki; Hiqma Nur Agustina (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Irgift is a micro, small, and medium enterprise in Gresik that has produced and sold artificial flower bouquets since 2020. Despite its growth, the business relies only on Instagram and WhatsApp for promotion, limiting market reach and reducing credibility. This study was carried out to design and develop a bilingual website integrated with social media as a promotional medium for Irgift. Using the Design and Development Research model with the ADDIE framework, the project involved analysis, design, development, implementation, and evaluation stages. Data were gathered through interviews, surveys, expert validation, and field testing. The website was created on the Wix platform with multilingual features, supported by intuitive layouts and an elegant color theme. Expert validation scored 82/100, while field testing with 35 respondents showed high satisfaction (88.6% strongly satisfied, average scores 4.4 - 4.8). Finally, the bilingual website enhances product visibility, customer trust, and marketing effectiveness, helping Irgift expand its market reach.